Case report: Outflow reconstruction with pre-frozen allograft blood vessels during in vivo partial hepatectomy followed by ex vivo tumor resection and partial liver autotransplantation for locally advanced hepatocellular carcinoma with background of cirrhosis - Chen, Jun-Ze; Zhang, Cheng; Su, Rui-Ling; Jian, Yong-Yuan; Huang, Kai-Yong; Tan, Xue-Lin; Chen, Zhao; Liao, Yong-Xin; Dong, Chun-Qiang; Dong, Kun (Frontiers in Oncology, 2024)
Ex vivo surgery and autotransplantation may provide a promising option for radical resection of conventionally unresectable liver tumors. Two cirrhotic patients with hepatocellular carcinoma (HCC), which has an “awkward seat” located in the “intrahepatic vascular triangle area (IVTA)” that consists of the middle hepatic vein (MHV), the right branches of the Glisson sheath, and the inferior vena cava (IVC), underwent in vivo extended right-half hepatectomy followed by ex vivo tumor resection and partial liver autotransplantation. Innovatively, the outflow of the tumor-free liver was reconstructed ex vivo using pre-frozen allograft blood vessels from brain-dead donors; the patients recovered well postoperation. We report the surgical experience to provide a novel curable surgical procedure for locally advanced IVTA liver tumors.